(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
The variation in Na+, K+ and Ca2+ ions levels in gills, muscle and liver of freshwater fish Cirrhinus mrigala exposed to lethal and sub lethal concentrations of cypermethrin were studied. A decreased trend was observed in all the tissues. But in sub lethal concentration at 21 day there is an improvement tendency was observed in present study.